Dedovanje po prejemniku denarne socialne pomoči - Žnidaršič Skubic, Viktorija (Delavci in delodajalci, 2012)
The paper presents the issue of limited access to the inheritance in cases when the state or the local community recourse to the assets of the testator if the latter received social assistance benefit while alive. The authoress first presents the types of social transfers which may be claimed back after the death of the recipient, provided certain statutory conditions are met, and then continues with an in-depth analysis of the Slovenian inheritance legislation covering this area.
Keywords: dedno pravo; dedovanje; denarna socialna pomoč; smrt; socialna pomoč